A Study on Firms with Negative Book Value of Equity. (18th March 2019) - Luo, Haowen; Liu, Ian; Tripathy, Niranjan
Abstract: This paper studies the puzzling negative book equity phenomenon among US public firms. Our evidence suggests that negative book equity firms exhibit heterogeneous characteristics. We show that a great portion of these firms, while operating at excessive capital structure with leverage ratio over 100%, are financially and operationally healthy. These healthy negative book equity firms increase their debt primarily motived by a need for funds to fulfill investment demand. We also find that the off‐balance sheet intangible assets and quality of intangible assets play an important role in determining the true debt capacity of these firms.